2010
DOI: 10.1182/blood-2009-10-249557
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of retinoic acid and scl controls primitive blood development

Abstract: Hematopoietic development during embryogenesis involves the interaction of extrinsic signaling pathways coupled to an intrinsic cell fate that is regulated by cell-specific transcription factors. Retinoic acid (RA) has been linked to stem cell self-renewal in adults and also participates in yolk sac blood island formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 42 publications
2
30
0
Order By: Relevance
“…This had enabled us to address specifically the mechanism of action of aldh, independent of the ATRA effects on dorsoventral patterning and vascular formation, which was often seen at pharmacological doses. [24][25][26] Second, the present study has suggested a complex mode of regulation of primitive hematopoiesis by aldh. We performed extensive gene expression profiling and functional screening for all 15 known zebrafish aldh isoforms.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…This had enabled us to address specifically the mechanism of action of aldh, independent of the ATRA effects on dorsoventral patterning and vascular formation, which was often seen at pharmacological doses. [24][25][26] Second, the present study has suggested a complex mode of regulation of primitive hematopoiesis by aldh. We performed extensive gene expression profiling and functional screening for all 15 known zebrafish aldh isoforms.…”
Section: Discussionmentioning
confidence: 53%
“…Very recently, de Jong et al 24 showed that DEAB treatment induced gata1 expression in wild type and partially rescued gata1 expression in the cdx4 mutant embryos. Remarkably, the rescue manifested only when the embryos were treated with DEAB between gastrulation and somitogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the embryonic lethality of compound RAR mutant mice it has not been possible to define the requirement for RAR signalling in erythropoiesis. Several reports provided evidence for a possible contribution of retinoid signalling in primitive erythropoiesis and the expression of erythropoietin (Kambe et al, 2000;de Jong et al, 2010).…”
mentioning
confidence: 99%
“…A series of experiments is summarized in Fig. 5.4(A) using cdx4 mutants, RA and an RA signaling inhibitor, in which gata1 expression was monitored (de Jong et al, 2010). These perturbations show that RA indirectly inhibits expression of gata1 and blocks erythropoiesis, and that this effect can be rescued by forced expression of scl, a direct activator of gata1 expression.…”
Section: Gene Regulatory Interactions In Primitive Erythropoietic Spementioning
confidence: 99%
“…5.3(A1), PLM) in the zebrafish embryo is established with respect to the anterior/posterior body axis downstream of expression of caudal genes (cdx4 and cdx1a). These cdx genes indirectly and redundantly affect primitive hematopoiesis in the posterior lateral mesoderm in two ways (Davidson and Zon, 2006;de Jong et al, 2010). Loss of cdx function (by mutation or morpholino treatment) precludes most primitive erythropoiesis.…”
Section: Gene Regulatory Interactions In Primitive Erythropoietic Spementioning
confidence: 99%